PEMBARUAN ARAH IMAN DAN LANGKAH PASTORAL (GEREJA DI NTT BELAJAR DARI PANDEMI COVID-19) - Chen, Martin (CREDENDUM: Jurnal Pendidikan Agama, 2022)
The Covid-19 pandemic has impacted the Catholic Church in the Province of NTT, Indonesia in various ways. Through social distance and safety protocols the worships must be restricted and even the church often must be shut. In a long and stable tradition, where the gathering and community of praying played a big role, it was a hard situation. More over in a misery situation, normally people could build community resilience as well as individual and spiritual resilience in the communal worship in the church. It was even lost during the pandemic situation. How might the church develop its pastoral learning of the Covid-19 Pandemic? It is not simply, to rechange the method of pastoral from “face to face form” to “online form”. Basically the church must reform its pastoral strategy. It should not be limited to liturgical services, but should cover all aspects of human life. Holistic pastoral care in the future must serve humanity in concrete screams of suffering and hope. Morely, the Church must place a compassionate Christ at the centre of its evangelisastion.